Overall Competence Through Training on Making Web and Flash Map Animations for Students in the City of Banda Aceh - Muhammad Wali; Taufiq Iqbal; Ismail Ismail; Arman Sah; Afrizal; Abdrurrazak (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
This training is based on the use of animation in learning which will greatly encourage students' enthusiasm for learning because it is supported by media which attracts the attention of young millennials. The problem that occurs is that not all students can develop learning by utilizing the web and animation as learning media. With these problems, of course, students are required to be able to implement web and animation in learning activities that can be used as a source of learning and get to know the world of the animation-making industry. To support students' abilities in the application of science and technology, especially those related to the use of technology in the use of web and animation for learning, students need to be trained to be skilled in web design and create simple animations. The results of the activities carried out are; There is an increase in student knowledge about the use of flash animation so that students can improve their mastery in developing and mastering Web Design and flash map animation and participants are also able to master the knowledge gained as additional skills and create their own job opportunities